(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This thesis examines microcirculation disorders in diabetes mellitus and modern strategies to correct them. It reviews molecular, cellular, and hemodynamic changes in diabetic microangiopathy, focusing on endothelial dysfunction, basement membrane thickening, and impaired autoregulation. Key factors include hyperglycemia-induced oxidative stress, advanced glycation products, and inflammation. Therapies like glycemic control, antioxidants, and targeted drugs show potential for restoring microcirculation. The study offers a clear framework for understanding and managing diabetic microvascular complications.